Faktor-Faktor Yang Berhubungan Dengan Persalinan Sectio Caesarea Di Rumah Sakit Umum Bali Royal Tahun 2023 - Putu Ayu Oktarini; Sri Rahayu; Ni Komang Erny Astiti (Midwifery Care Journal, 2024)
The issues with the mother and child led to the possibility of a sectio cesarean delivery. To save the mother and fetus, the Sectio Cesarean method was employed. The research's objective was to identify the variables linked to cesarean section deliveries at Bali Royal General Hospital in 2023. such as cross-sectional correlational analytical study. Every mother who gave birth in 2023 was included in the research population. Purposive sampling was used to obtain a sample size of 84. use of chi-square data analysis. Mothers who are not at risk are more likely to give birth spontaneously behind the head, according to the study's findings. Meanwhile, CS affected 49 individuals, or 94.2% of the moms at risk. The p value is 0.001 0.05. More primigravida mothers gave birth via posterior birth, namely 11 people (73.3%). Multigravida mothers more often give birth by SC. The p value was 0.002 0.05. that the pregnancies ≤ 2 years apart were more likely to give birth by CS, namely 47 people (81%) while those 2 were more likely to give birth spontaneously behind the head. The p value is 0.001 0.05. fetuses that experience emergencies in all types of delivery by SC. The p value was 0.001 0.05. The conclusion was that there was a relationship between age, parity, gestational spacing and fetal distress with the incidence of CS. Pregnant women should regularly monitor their health during pregnancy and prepare for childbirth.